(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Ashmari is considered as Mahagada being difficult to cure, marmaashrayi and involvement of Bahu dosha. Ashmari is tridoshaja in origin. Basti is vyakta stana of Ashmari and basti is also a pranayatana. It is a fatal disease as it needs surgical intervention. On prognosis this disease is kruchasaadhya. Now in this era, there are many treatment modalities like Flush out Therapy and Surgical procedure are developed in this regard but failed in treating the root cause and recurrence of disease, as these procedures cannot avoid the pathogenesis behind the formation of stone results in recurrence of stone which is becoming a great problem and constant efforts are being made to evolve an effective treatment as well as prevention and recurrence of disease. It is the time for the medical science to give it’s best to treat the condition effectively. In this connection it is postulated that Anand Yoga is one of the herbal compound which is having lithotriptic action and can be used as paniya kshara and also be used at OPD level and economical also.